2015
DOI: 10.3928/1081597x-20150727-05
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Collamer Lens for Myopia: Assessment 12 Years After Implantation

Abstract: The ICL PIOL provided good refractive outcomes and stability in the long term. The incidence of cataracts is low when the latest models of this PIOL are used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
2
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 42 publications
5
80
2
7
Order By: Relevance
“…; Moya et al. ). We attributed this result to the different subjects; the anisometropic myopia patients in our study were different from the common myopia patients included in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…; Moya et al. ). We attributed this result to the different subjects; the anisometropic myopia patients in our study were different from the common myopia patients included in other studies.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, there are no published results in the literature concerning long-term follow-up of the phakic IOL used in our study. However, the implantable collamer lens (ICL) is very similar, and there are reports of 10 years of follow-up with the ICL (15,16). Fernández-Vega-Cueto et al (17) found that prior to implantation of the Visian ICL (Staar Surgical AG, Nidau, Switzerland), the mean SE was -8.30±2.98 D; after surgery, it was -0.19±0.32 D, -0.29±0.38 D, and -0.37±0.47 D at 12, 24, and 36 months, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple long-and shortterm studies have provided solid evidence of the safety, effectiveness and predictability of posterior chamber ICL implantation surgery. In a 12-year retrospective clinical study comprising 140 eyes, Moya et al (2015) reported a significant improvement of visual acuity in high myopia patients underwent ICL implantation surgery with low incident of postoperative complications. Igarashi also depicted 93% of eyes were within AE1.0 D of the intended correction 4 years after ICL implantation, demonstrating a good predictability (Igarashi et al 2014).…”
Section: Introductionmentioning
confidence: 99%